Differences on Job Satisfaction among Technical and Vocational Education and Training Schools Employees in Kathmandu - Rimal, Ishwor (Journal of Technical and Vocational Education and Training, 2021)
Job satisfaction is crucial for occupations such as instructors and admin staff of the Technical and Vocational Education and Training (TVET) schools. In this context, this study explored the level of TVET school employees' job satisfaction and differences by educational qualification among the sampled employees of Council for Technical Education and Vocational Training (CTEVT) constituted TVET Schools in Kathmandu, using quantitative research method. The SPSS was used for the data analysis of the study. The results of overall job satisfaction of the TVET employees showed moderate level, which also means that the level of job satisfaction yet not at satisfactory level. This demands a specific strategy to motivate them and increase the level of job satisfaction. The higher the academic qualification of the TVET employees was lower level job satisfaction. It indicates that other attributing factors are also necessary to consider for job satisfaction of the TVET employees. The social capital theory was used to analyze and discuss the results.